Phytochemical Screening and Mineral Contents of Annual Plants Growing Wild in the Southern of Tunisia - Zammouri, HÃ©di Mighri, Mohamed Neffati, Ahmed Akrout, Hajer El Jani, Tarek (Journal of Phytology, 2009)
Eight annual species growing wild in the southern of Tunisia (Diplotaxis simplex, Chrysanthemum coronarium, Matthiola longipetela, Erodium glaucophyllum, Reseda alba, Diplotaxis harra, Senecio gallicus and Papaver rhoeas) were evaluated for their mineral contents and phytochemical screening. The mineral analysis showed that calcium and potassium were the most concentrated minerals (1.21-3.60% and 0.36-3.20% respectively) followed by sodium (0.12-1.38%), magnesium (0.16-0.41%) and phosphorus (0.05-28%). The preliminary phytochemical screening revealed the absence of anthraquinones in all studied plants whereas alkaloids were only present in Papaver rhoeas. Senecio gallicus and Chrysanthemum coronarium were the only species that contained essential oils. All species were found to contain saponins, flavonoids and tannins with the exception of Erodium glaucophyllum and Papaver rhoeas.Ã‚Â These results indicate that some of these species may be used as fodder plants for livestock due to their high contents of minerals but the presence of some secondary metabolites may reduce their palatability. In the other hand, these secondary metabolites could be the origin of the medicinal properties of these species.Ã‚Â Ã‚Â